Characterization of an energy efficient pulsed current TIG welding process on AISI 316 and 304 stainless steels - Rosario Casanueva; Christian Brañas; F. Javier Diaz; Francisco J. Azcondo; Diego Ferreño; Jesus Setien (Heliyon, 2023)
This paper presents the characterization of a TIG welding process carried out by means of an arc welding power supply able to provide dc or pulsed current. The arc welding power supply is based on resonant power converters and an FPGA-based control circuit. Dc and multiple pulsed operations up to 1 kHz with different pulse widths have been tested. The operation of the proposed welding power supply has been compared to that of a high-quality commercial welding machine. Regarding performance, the investigated electrical parameters are: power factor, power conversion efficiency and the energy consumption of the process. The radiography and mechanical properties of the welds have been examined. The mechanical properties of the welded joints characterized through tensile tests are the yield stress, tensile strength and the strain under maximum stress. In addition, the impact properties of the joints were determined through Charpy tests and the curves relating energy absorbed and temperature were obtained. The results show an improved performance of the proposed arc welding power supply over the commercial counterpart, with higher efficiency and power factor, as well as lower energy consumption. The yield stress and tensile strength results indicate that the welded plates using pulsed modes with the proposed power supply are comparable to the reference weld performed with dc operation using the commercial welder. Remarkably, it was observed that the ductility of the welded plates using pulsed modes with the proposed power supply outperforms those of the reference weld carried out with dc arc using the commercial welder.